1998
DOI: 10.1099/0022-1317-79-10-2381
|View full text |Cite
|
Sign up to set email alerts
|

The antiviral compound ribavirin modulates the T helper (Th) 1/Th2 subset balance in hepatitis B and C virus-specific immune responses.

Abstract: Ribavirin is effective in combination therapies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
167
0
7

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(184 citation statements)
references
References 42 publications
10
167
0
7
Order By: Relevance
“…[31][32][33][34][35] This dual effect may help in the control of chronic HBV infection, and thus oral ribavirin might be useful as an adjunctive therapy for chronic hepatitis B. Previous studies have shown that a 6-month course of ribavirin alone or in combination with IFN-␣ modestly inhibit HBV replication with a variable rate of serum ALT normalization and HBeAg seroconversion.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34][35] This dual effect may help in the control of chronic HBV infection, and thus oral ribavirin might be useful as an adjunctive therapy for chronic hepatitis B. Previous studies have shown that a 6-month course of ribavirin alone or in combination with IFN-␣ modestly inhibit HBV replication with a variable rate of serum ALT normalization and HBeAg seroconversion.…”
Section: Discussionmentioning
confidence: 99%
“…The same study demonstrated a predominant Th2 pattern with higher circulating levels of IL-6, IL-10 and TNF-α in HCV+ patients compared to HCV-patients, possibly reflecting a more active systemic inflammatory response. On the other hand, modifications in the Th1/Th2 ratio provoked by ribavirin treatment leading to an imbalance towards the Th1 response may be associated with a more favorable outcome regarding HCV therapy (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…[80][81][82][83] In addition, ribavirin has been shown to downregulate Th2 mediated antibody production to HbeAg in mice. 84 Because ribavirin induced a Th1 cytokine profile it was possible that it might influence susceptibility to IIT in patients with HCV treated with the combination of IFN␣ and ribavirin. One recent study examined this possibility.…”
Section: Non-genetic Factorsmentioning
confidence: 99%